Preparation method of flame-retardant, high-refraction and melt-drop-resistant acrylate resin coating

By introducing components such as amide carbon nanotubes, bis(2-ethylhexanoate) hydroxyaluminum, DOPO and N-vinyl carbazole into the acrylate resin, the problems of low oxygen index and low refractive index during combustion of acrylate resins are solved, and the effects of high flame retardancy and high refractive index are achieved, and it is suitable for high-performance optical materials.

CN119875459AActive Publication Date: 2025-04-25YANTAI UNIV

Patent Information

Application Number
CN202510326787.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-25
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

Acrylate resins have low oxygen index during combustion, which is prone to melt droplets and smoke, and at the same time, the refractive index is also low, affecting the performance of optical devices.

Method used

By introducing components such as aminolated carbon nanotubes, bis(2-ethylhexanoate) hydroxyaluminum, DOPO and N-vinyl carbazole, acrylate resins are modified to enhance their carbon layer density and flame retardant properties, and the refractive index is increased by dimercaptothiadiazole.

Benefits of technology

It significantly improves the flame retardancy and refractive index of acrylate resins, reduces the generation of melt droplets, enhances its heat resistance in high-oxygen environments, and is suitable for high-performance optical materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a flame-retardant, high-refraction and melt-drop-resistant acrylate resin coating, which comprises the following steps: adding water, an emulsifier and methacrylic acid into a reaction container, stirring for reaction, and then adding a monomer A, DOPO and N-vinylcarbazole; heating to 75-85 DEG C, dropwise adding an initiator, and reacting for 1-2 hours to obtain a core-layer emulsion; the preparation method comprises the following steps: adding a monomer A and a monomer B into a reaction kettle, simultaneously dropwise adding all the monomer B and an initiator, stirring and reacting for 1-2 hours, adding DOPO, cooling to 50 DEG C, adding an emulsifier B, reacting for 30-60 minutes, adding N-vinyl carbazole, reacting for 0.25-0.5 hour, adding an ammonium polyphosphate solution, aluminum sulfate and chitosan / gelatin composite microspheres, shearing and emulsifying at a high speed, and adjusting the pH value to 7-8 to obtain the flame-retardant, high-refraction and melt-drop-resistant water-based acrylate resin coating. The obtained acrylate resin coating has the advantages of high oxygen index, no molten drop during combustion and high film refractive index.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a water-based acrylic resin coating, in particular to a method for preparing a flame-retardant, high-refractive and drip-resistant water-based acrylic resin coating. Background Art

[0002] In recent years, intelligent optoelectronic devices such as flexible displays and micro-sensors are in a rapid development stage, and high-performance optical materials are the basis for realizing the functions of advanced optical devices. Although traditional inorganic optical materials have advantages such as high strength, high refractive index, and low dispersion, their disadvantages of high brittleness, high weight, and high processing difficulty limit their application in advanced optical devices. Organic optical materials have become the preferred materials for advanced optical devices due to their advantages such as adjustable performance, light texture, and easy processing. They are used in high-performance substrates, packaging materials for light-emitting diodes (LEDs), and microlenses for charge-coupled devices (CCDs) or complementary metal oxide semiconductor (CMOS) image sensors. However, compared with inorganic optical materials, the molecular structure characteristics of organic optical materials lead to poor thermal stability and low refractive index. Among them, the refractive index is the most critical parameter of organic optical materials. The disadvantage of low refractive index hinders the progress of high-precision optical devices.

[0003] Yunhui Tang et al. synthesized three acrylate monomers (M-1, M-2 and M-3) with different chemical structures (fluorene group, thiadiazole and diphenyl sulfide group) through a simple one-step method, and prepared acrylate polymers P-1, P-2 and P-3 by free radical melt polymerization. Their thermal stability is higher than 250°C, and their refractive indices are 1.62, 1.61 and 1.64 (550nm), respectively. The transmittance at a wavelength of 450nm is more than 90%, but the P-2 film is light yellow, which comes from the polar thiadiazole causing the molecular chains to be arranged regularly and the chromophores to aggregate, thereby producing color and reducing the transmittance. In addition, there is no water-based acrylate resin emulsion used in organic optical materials.

[0004] Invention patent CN111303478A relates to naked-eye 3D display screen materials and preparation methods thereof, the method comprising the following steps: providing a polymer solution in which a base material is dissolved in a volatile solvent, wherein the base material is an optically transparent material and the volatile solvent is immiscible with water; casting the polymer solution on an optically transparent substrate in a constant temperature and humidity sealed container, promoting the nucleation and growth of water droplets on the surface of the polymer solution by the volatilization of the volatile solvent; placing the optically transparent substrate cast with the polymer solution in a constant temperature and humidity sealed container, and after the volatile solvent and water droplets are completely volatilized, a microscopic structure of spherical pits left by water droplets is formed on the surface of the base material, thus obtaining a naked-eye 3D display screen material, the resin material used is mainly self-polystyrene-butadiene-styrene block copolymer, polycarbonate, polyethyleneimine or polymethyl methacrylate, and its light transmittance is less than 95%, the invention patent does not emphasize flame retardancy and droplet resistance in terms of heat resistance, and pure methyl methacrylate is used as a monomer, and no composite acrylate monomer is used.

[0005] Regarding flame retardancy, relevant research has been reported. Invention patent CN118931301A involves a method for preparing a flame-retardant, washable, and moderately compatible water-based acrylic resin coating. Water, emulsifier, and methacrylic acid are added, stirred and reacted for 60 minutes, and then monomer A, carbon-forming agent intermediate, DOPO, and 3,4-epoxy-1-butene are added, and the emulsification time is 20 to 30 minutes; the temperature is raised to 80 to 90°C, an initiator is added dropwise, and the reaction is carried out for 1 to 2 hours, and then diethanolamine is added and the reaction is carried out for 1 to 2 hours to obtain a core layer emulsion; at the same time, monomer B and an initiator are added dropwise, and the reaction is stirred at 75 to 85°C for 1.5 hours, and then the reaction is carried out. DOPO, 3,4-epoxy-1-butene and initiator are reacted at 60-70°C for 1 hour, cooled to 50°C, emulsifier B is added, the reaction time is 30 minutes, and ammonia water is added to adjust the pH value to 7-8 to obtain a flame-retardant, washable, moderately compatible water-based acrylic resin coating. The obtained acrylic resin has good flame retardancy and water washability. The invention patent has good flame retardancy, but does not involve high refraction, and the acrylic resin does not characterize the flame retardant oxygen index. There is still room for improvement in pkHHR. Due to the long-term use of electrical components, a large amount of heat will be released, resulting in a decrease in its refractive index and flame retardancy, so it needs to be further improved.

[0006] At present, acrylic resins used in optical materials have a low refractive index and shrinkage after curing, which requires re-filming. In addition, optical instruments release a lot of heat when used for a long time, so flame retardancy and melt droplet indicators need to be considered. Therefore, it is imperative to develop high-refractive-index acrylic resin materials. Summary of the invention

[0007] The present invention aims to solve the problem that the oxygen index of acrylic resin is low and the combustion generates molten droplets and smoke, and also solves the defect of low refractive index of acrylic resin. In addition, since the acrylic resin is first used at high temperature and then at room temperature during the film-forming process, the area of ​​the film partially shrinks during cooling due to the influence of the traditional thermal expansion and contraction principle, which affects the surface smoothness. Based on this, phosphorus trichloride is used to enhance the acidity in the heating environment, so that the density of the carbon layer formed by the carbon nanotubes is enhanced, and bis(2-ethylhexanoic acid) hydroxyaluminum plays a role in enhancing the density of the carbon layer of the carbon nanotubes, so that the molten droplets of acrylic resin are reduced, and the oxygen generated by the heated combustion is reduced. Aluminum oxide has good thermal conductivity, which improves the flame retardancy of carbon nanometers and the flame retardancy of acrylic resins; dimercaptothiadiazole, which is a nitrogen-sulfur heterocyclic compound, is selected to react with acryloyl chloride to obtain an acrylic monomer containing double bonds and nitrogen and sulfur on the main chain, which is then introduced into the chain segment of the acrylic resin, and the acrylic monomer modified with the refractive group is used in the core layer and shell layer of the acrylic resin, thereby improving the refractive index of the overall acrylic resin; at the same time, the advantage of the microspheres having a small decrease in shrinkage under dry conditions is utilized to reduce the decrease in the shrinkage of the acrylic resin film at room temperature, thereby facilitating industrial production.

[0008] The preparation method of the flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating is prepared according to the following steps: (1) Preparation of core layer emulsion: Add 500-700 g of water, 13-19 g of emulsifier A, and 25-45 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 50-55°C, stir and react for 30-60 min, then add monomer A, 13.4-14.5 g of DOPO, and 0.4-0.6 g of N-vinyl carbazole, and emulsify for 30-40 min; heat to 65°C, pass reflux water, heat to 75-85°C, dropwise add 12-14 g of initiator, dropwise add for 0.5-1.5 h, react for 1-2 h, and obtain core layer emulsion; (2) To the core layer emulsion obtained in step (1), monomer B and 10-14 g of initiator are simultaneously added dropwise for 1-1.5 h, and the mixture is stirred at 70-85 °C for 1-2 h. Then 6.9-12.2 g of DOPO are added, and the mixture is reacted at 70-80 °C for 1-2 h. The mixture is cooled to 50 °C, and 14-21 g of emulsifier B is added for 30-60 min. Then 0.5-0.6 g of N-vinyl carbazole is added for 0.25-0.5 h. Then 14.2 g of ammonium polyphosphate solution dissolved in 10 g of water, 0.5-1.3 g of aluminum sulfate, 0.1-0.2 g of ammonium molybdate and 0.5-0.8 g of chitosan / gelatin composite microspheres are added. 1000-2000 At a speed of r / min, high-speed shear emulsification is performed for 0.5-1h, and when the foam disappears, ammonia water is added to adjust the pH value to 7-8 to obtain a flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating; The monomer A is prepared by mixing 20-35g of ethyl acrylate, 22-38g of methyl methacrylate, 18-32g of hydroxyethyl acrylate, 6-12g of amino carbon nanotubes, and 3.4-6.2g of high refractive material; The monomer B is prepared by mixing 8-14g of amino carbon nanotubes, 12-54g of methyl methacrylate, 55-92g of hydroxyethyl acrylate and 3.2-5.8g of high refractive material.

[0009] The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2.5:1.

[0010] The method for preparing the amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2 to 3 h in the presence of 100 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 to 4:1. After ultrasonic treatment, the carbon nanotube solution was diluted with 100 mL of water, the acid solution was filtered with a vacuum pump, washed with deionized water until neutral, and dried at 100 to 105°C overnight to obtain carboxylated carbon nanotubes. 3.6 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.2 to 0.4 g of carboxylated carbon nanotubes and 4.5 to 4.7 g of bis(2-ethylhexanoic acid) hydroxyaluminum were added, reacted at 50 to 60°C for 30 to 60 min, then placed in a constant temperature oil bath at 70 to 80°C, 7.7 to 9.4 g of acrylamide were added and reacted for 2 to 4 h, washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried overnight at 100 to 105°C in vacuum to obtain amino carbon nanotubes.

[0011] The initiator is any one of ammonium persulfate and potassium persulfate.

[0012] The preparation method of the high-refractive material is as follows: under a nitrogen atmosphere, 7.3 g of dithiothiadiazole is uniformly dissolved in 40 mL of anhydrous dichloromethane, 22 mL of triethylamine and 2.2-2.9 g of phthalic anhydride are added, and the mixture is stirred at -5°C for 0.5-1 h. A dropping funnel is used to slowly drop 20 mL of a mixed solution of acryloyl chloride and dichloromethane in a volume ratio of 1:1, and the mixture is reacted at room temperature for 24 h. The solution is then extracted 2-3 times with a 10% HCl aqueous solution to neutralize excess triethylamine, and then extracted 2-3 times with a saturated sodium chloride aqueous solution to obtain a high-refractive material.

[0013] The emulsifier B is AEO-9.

[0014] Preparation method of chitosan / gelatin composite microspheres: (1) Dissolve 5-6 g of chitosan in 50 mL of 4% acetic acid aqueous solution, and dissolve 3-4 g of gelatin in 40 mL of deionized water at 55°C. Then mix the chitosan aqueous solution and the gelatin aqueous solution to form a chitosan / gelatin mixed solution. (2) Add 30 mL of paraffin and 5 g of span80 into a three-necked flask, heat to 50-60° C., stir for 15-30 min, and slowly drip the chitosan / gelatin mixture from step (1) into the three-necked flask using a separatory funnel for 15 min. Emulsify at 60-70° C. for 30-40 min. After emulsification, quickly cool to 20° C., add 1 mL of 50% by mass glutaraldehyde, and solidify for 0.5-1 h. After solidification, centrifuge and collect the composite microspheres using a high-speed centrifuge, wash with acetone and isopropanol, and then dry to obtain chitosan / gelatin composite microspheres.

[0015] The positive effects of the present invention are: (1) The present invention constructs a flame retardant, high refractive, and drip-resistant water-based acrylic resin coating, which aims to solve the problem that the oxygen index of acrylic resin is low during combustion and that it is easy to produce drips and smoke during combustion. At the same time, it also makes up for the defect of low refractive index of acrylic resin. Since the acrylic resin is first used at high temperature and then at room temperature during the film-forming process, the area of ​​the film partially shrinks during cooling, affecting the surface smoothness. Based on this, phosphorus trichloride is used to enhance the acidity in the heating environment, thereby enhancing the density of the carbon layer formed by the carbon nanotubes. Bis(2-ethylhexanoic acid) hydroxyaluminum plays a role in enhancing the density of the carbon layer of the carbon nanotubes, causing the acrylic resin drips to drop. The aluminum oxide produced by its heated combustion is itself a good thermal conductive material, which improves the flame retardancy of carbon nanotubes. DOPO cooperates with N-vinyl carbazole to produce a free radical reaction, thereby improving the flame retardancy of acrylic resin from the chain segment. DOPO cooperates with N-vinyl carbazole carbonizing agent to solve the problem of acrylic resin. When the film burns, melt droplets are generated. The oxygen index of the acrylic film is 26%, while the oxygen index of the acrylic film can exceed 29% by using DOPO in conjunction with N-vinyl carbazole and APP for flame retardancy. Aluminum sulfate and ammonium molybdate are complexed with APP to improve the dispersion stability of APP and the stability of the acrylic resin emulsion. At the same time, N-vinyl carbazole can also assist in improving the refractive index of the resin. Dithiothiadiazole, a nitrogen-sulfur heterocyclic compound, is selected to react with acryloyl chloride to obtain an acrylic monomer containing double bonds and nitrogen and sulfur on the main chain, which is then introduced into the chain segment of the acrylic resin. The acrylic monomer modified with the refractive group is used in the core layer and shell layer of the acrylic resin to improve the refractive index of the acrylic resin. At the same time, the shrinkage rate of the microspheres under dry conditions decreases slightly, and the shrinkage rate of the acrylic resin film at room temperature is reduced, which is convenient for industrial production.

[0016] (2) The amino modified carbon nanotube is a compound in which a dense carbon layer is introduced into the molecular chain of acrylamide; the amino modified carbon nanotube is a carbon nanotube that produces a large number of hydroxyl groups and carboxyl groups on the surface of the carbon nanotube under the strong acid oxidation conditions of sulfuric acid and nitric acid. Since the traditional carbon nanotube is thin and light, it can cause the droplet to fall when used in the water-based acrylic resin film, but it does not significantly increase its oxygen index. Therefore, it is necessary to improve the density of the product during combustion so that the carbon layer can bear the heat of combustion in a high oxygen content environment. The present invention uses phosphorus trichloride and carboxylated carbon nanotubes and di(2-ethylhexanoic acid) to form a carbon nanotube. ) Some hydroxyl groups in hydroxyaluminum react with carboxyl groups to introduce acyl chloride bonds into the system, and then react with acrylamide to introduce double bond groups into the system. Under the action of an initiator, the carbon-forming part can be introduced into the molecular chain of acrylic resin with acrylic monomers. In this reaction, phosphorus trichloride enhances the acidity under heating environment, thereby enhancing the density of the carbon layer formed by the carbon nanotubes, while bis(2-ethylhexanoic acid)hydroxyaluminum enhances the density of the carbon layer of the carbon nanotubes, and the aluminum oxide produced by its combustion under heating is a good thermal conductor, which improves the flame retardancy of the carbon nanotubes, thereby improving the flame retardancy of the acrylic resin.

[0017] (3) The present invention selects dithiothiadiazole, which is a nitrogen-sulfur heterocyclic compound. In the alkaline environment of triethylamine, the hydrogen of the SH group is ionized to open the anhydride ring of phthalic anhydride. The remaining SH reacts with acryloyl chloride to obtain an acrylic monomer containing double bonds and nitrogen and sulfur on the main chain. The acrylic monomer is then introduced into the chain segment of the acrylic resin, so that the monomer unit with high refractive index can be more evenly distributed in the acrylic resin chain segment, thereby improving the refractive index of the acrylic resin chain segment. At the same time, in order to make the distribution of the refractive monomer unit more uniform, the acrylic monomer modified with the refractive group is used in the core layer and shell layer of the acrylic resin, thereby improving the refractive index of the overall acrylic resin.

[0018] (4) The present invention uses a chitosan and gelatin composite system under glutaraldehyde curing conditions to synthesize chitosan / gelatin composite microspheres. The microspheres have a small shrinkage rate reduction under dry conditions, which reduces the shrinkage of acrylic resin films at room temperature, thereby facilitating industrial production. DETAILED DESCRIPTION Embodiment 1

[0019] The preparation method of the flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating is prepared according to the following steps: (1) Preparation of core layer emulsion: add 500 g of water, 13 g of emulsifier A (sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2.5: 1), and 25 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 50°C, stir and react for 30 min, then add monomer A, 13.4 g of DOPO and 0.4 g of N-vinyl carbazole, and emulsify for 30 min; heat to 65°C, pass reflux water, heat to 75°C, add 12 g of ammonium persulfate initiator (20 g dissolved in water), add for 0.5 h, and react for 1 h to obtain core layer emulsion; (2) To the entire core layer emulsion obtained in step (1), monomer B and 10 g of initiator (10 g dissolved in water) were added dropwise for 1 h, and the mixture was stirred at 70°C for 1 h. Then 6.9 g of DOPO was added and the mixture was reacted at 70°C for 1 h. The mixture was cooled to 50°C, and 14 g of AEO-9 emulsifier B was added for 30 min. Then 0.5 g of N-vinyl carbazole was added and the mixture was reacted at 70°C for 0.25 h. Then 14.2 g of ammonium polyphosphate solution dissolved in 10 g of water, 0.5 g of aluminum sulfate, 0.1 g of ammonium molybdate and 0.5 g of chitosan / gelatin composite microspheres were added at 40°C. The mixture was emulsified at a high speed of 1000 r / min for 0.5 h. After the foam disappeared, ammonia water was added to adjust the pH to 7-8 to obtain a flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating. The monomer A is prepared by mixing 20 g of ethyl acrylate, 22 g of methyl methacrylate, 18 g of hydroxyethyl acrylate, 6 g of amino carbon nanotubes, and 3.4 g of high refractive material; The monomer B is prepared by mixing 8 g of amino carbon nanotubes, 12 g of methyl methacrylate, 55 g of hydroxyethyl acrylate, and 3.2 g of a high refractive material.

[0020] The method for preparing the amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2 h in concentrated sulfuric acid and 100 mL of concentrated nitric acid in a volume ratio of 3: 1. After ultrasonication, the carbon nanotube solution was diluted with 100 mL of water, the acid solution was filtered with a vacuum pump, washed with deionized water until neutral, and dried at 100° C. overnight to obtain carboxylated carbon nanotubes; 3.6 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.2 g of carboxylated carbon nanotubes and 4.5 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, and the mixture was reacted at 50° C. for 30 min, then placed in a 70° C. constant temperature oil bath, 7.7 g of acrylamide was added, and the mixture was reacted for 2 h, and washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried at 100° C. overnight in vacuum to obtain amino carbon nanotubes.

[0021] The preparation method of the high-refractive material is as follows: under a nitrogen atmosphere, 7.3 g of dithiothiadiazole is uniformly dissolved in 40 mL of anhydrous dichloromethane, 22 mL of triethylamine and 2.2 g of phthalic anhydride are added, and the mixture is stirred at -5°C for 0.5 h. A dropping funnel is used to dropwise add 20 mL of a mixed solution of acryloyl chloride and dichloromethane in a volume ratio of 1:1, and the mixture is reacted at room temperature for 24 h. The reaction solution is extracted twice with a 10% HCl aqueous solution to neutralize excess triethylamine, and then extracted twice with a saturated sodium chloride aqueous solution to obtain a high-refractive material.

[0022] Preparation method of chitosan / gelatin composite microspheres: (1) Dissolve 5 g of chitosan in 50 mL of 4% acetic acid aqueous solution, and dissolve 3 g of gelatin in 40 mL of deionized water at 55°C. Then mix the chitosan aqueous solution and the gelatin aqueous solution to form a chitosan / gelatin mixed solution. (2) Add 30 mL of paraffin and 5 g of span80 into a three-necked flask, heat to 50°C, stir for 15 min, and use a separatory funnel to drop the chitosan / gelatin mixed solution from step (1) into the three-necked flask. The dropping time is 15 min. Emulsify at 60°C for 30 min. After the emulsification is completed, quickly cool to 20°C, add 1 mL of 50% by mass glutaraldehyde, and solidify for 0.5 h. Centrifuge and collect the composite microspheres in a high-speed centrifuge, wash with acetone and isopropanol, and then dry to obtain chitosan / gelatin composite microspheres. Embodiment 2

[0023] The preparation method of the flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating is prepared according to the following steps: (1) Preparation of core layer emulsion: add 700 g of water, 19 g of emulsifier A (sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2.5: 1), and 45 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 55°C, stir and react for 60 min, then add monomer A, 14.5 g of DOPO, and 0.6 g of N-vinyl carbazole, and emulsify for 40 min; heat to 65°C, pass reflux water, heat to 85°C, add 14 g of potassium persulfate initiator (dissolved in 20 g of water), add for 1.5 h, and react for 2 h to obtain core layer emulsion; (2) To the whole core layer emulsion obtained in step (1), all monomers B and 14 g potassium persulfate initiator (dissolved in 14 g water) were added dropwise at the same time for 1.5 h. The mixture was stirred at 85 °C for 2 h. Then 12.2 g DOPO was added and the mixture was reacted at 80 °C for 2 h. The mixture was cooled to 50 °C and 21 g AEO-9 emulsifier B was added for 60 min. Then 0.6 g N-vinyl carbazole was added and the mixture was reacted for 0.5 h. Then 14.2 g ammonium polyphosphate solution dissolved in 10 g water, 1.3 g aluminum sulfate, 0.2 g ammonium molybdate and 0.8 g chitosan / gelatin composite microspheres were added. The mixture was emulsified at a high speed of 2000 r / min for 1 h. After the foam disappeared, ammonia water was added to adjust the pH to 7-8 to obtain a flame retardant, high refractive, and drip-resistant water-based acrylic resin coating. The monomer A is prepared by mixing 35g of ethyl acrylate, 38g of methyl methacrylate, 32g of hydroxyethyl acrylate, 12g of amino carbon nanotubes, and 6.2g of high refractive material; The monomer B is prepared by mixing 14 g of amino carbon nanotubes, 54 g of methyl methacrylate, 92 g of hydroxyethyl acrylate, and 5.8 g of a high-refractive material.

[0024] The method for preparing the amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 3 h in the presence of 100 mL of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 4:1. After ultrasonication, the carbon nanotube solution was diluted with 100 mL of water, filtered with a vacuum pump, washed with deionized water until neutral, and dried at 105°C overnight to obtain carboxylated carbon nanotubes. 3.6 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.4 g of carboxylated carbon nanotubes and 4.7 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, and the mixture was reacted at 60°C for 60 min. Then, 9.4 g of acrylamide was added in a constant temperature oil bath at 80°C and reacted for 4 h. The mixture was washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and dried at 105°C in vacuum overnight to obtain amino carbon nanotubes.

[0025] The preparation method of the high-refractive material is as follows: under a nitrogen atmosphere, 7.3 g of dithiothiadiazole is uniformly dissolved in 40 mL of anhydrous dichloromethane, 22 mL of triethylamine and 2.9 g of phthalic anhydride are added, and the mixture is stirred at -5°C for 0.5 to 1 h. A dropping funnel is used to slowly drop 20 mL of a mixed solution of acryloyl chloride and dichloromethane in a volume ratio of 1:1. The mixture is reacted at room temperature for 24 h, and the solution is extracted 2 to 3 times with a 10% HCl aqueous solution to neutralize excess triethylamine, and then extracted 2 to 3 times with a saturated sodium chloride aqueous solution to obtain a high-refractive material.

[0026] Preparation method of chitosan / gelatin composite microspheres: (1) Dissolve 6 g of chitosan in 50 mL of 4% by mass acetic acid aqueous solution, and dissolve 4 g of gelatin in 40 mL of deionized water at 55°C, and then mix the chitosan aqueous solution and the gelatin aqueous solution to form a chitosan / gelatin mixed solution; (2) Add 30 mL of paraffin and 5 g of span80 into a three-necked flask, heat to 60°C, stir for 30 min, and use a separatory funnel to drop the chitosan / gelatin mixed solution in step (1) into the three-necked flask. The dropping time is 15 min. Emulsify at 70°C for 40 min. After the emulsification is completed, quickly cool to 20°C, add 1 mL of 50% by mass glutaraldehyde, and solidify for 1 h. After the solidification is completed, centrifuge and collect the composite microspheres using a high-speed centrifuge, wash with acetone and isopropanol, and then dry to obtain chitosan / gelatin composite microspheres. Embodiment 3

[0027] The preparation method of the flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating is prepared according to the following steps: (1) Preparation of core layer emulsion: add 600 g of water, 16 g of emulsifier A (mixed with sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2.5:1), and 35 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 50°C, stir and react for 45 min, then add monomer A, 14 g of DOPO and 0.5 g of N-vinyl carbazole, and emulsify for 35 min; heat to 65°C, pass reflux water, heat to 80°C, add 13 g of ammonium persulfate initiator (dissolved in 20 g of water), add for 1 h, and react for 1.5 h to obtain core layer emulsion; (2) To the whole core layer emulsion obtained in step (1), all monomers B and 12 g of ammonium persulfate initiator (dissolved in 20 g of water) were added dropwise at the same time. The addition time was 1 hour. The mixture was stirred at 75°C for 1.5 hours. Then 9.5 g of DOPO was added. The mixture was reacted at 75°C for 1.5 hours. The mixture was cooled to 50°C. 17.5 g of AEO-9 emulsifier B was added. The reaction time was 45 minutes. Then 0.55 g of N-vinyl carbazole was added. The mixture was reacted for 0.35 hours. Then 14.2 g of ammonium polyphosphate solution dissolved in 10 g of water, 0.9 g of aluminum sulfate, 0.15 g of ammonium molybdate and 0.65 g of chitosan / gelatin composite microspheres were added. The mixture was emulsified at a high speed of 1500 r / min for 0.75 hours. After the foam disappeared, ammonia water was added to adjust the pH value to 7-8 to obtain a flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating. The monomer A is prepared by mixing 27.5 g of ethyl acrylate, 30 g of methyl methacrylate, 25 g of hydroxyethyl acrylate, 9 g of amino carbon nanotubes, and 4.8 g of high refractive material; The monomer B is prepared by mixing 11 g of amino carbon nanotubes, 33 g of methyl methacrylate, 73.5 g of hydroxyethyl acrylate, and 4.5 g of a high refractive material.

[0028] The method for preparing the amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2.5 h in concentrated sulfuric acid and 100 mL of concentrated nitric acid in a volume ratio of 3.5: 1. After ultrasonication, the carbon nanotube solution was diluted with 100 mL of water, vacuum-filtered, washed with deionized water until neutral, and dried at 100° C. overnight to obtain carboxylated carbon nanotubes. 3.6 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.3 g of carboxylated carbon nanotubes and 4.6 g of bis(2-ethylhexanoic acid)hydroxyaluminum were added, and the mixture was reacted at 55° C. for 45 min. Then, the mixture was placed in a 75° C. constant temperature oil bath, 8.5 g of acrylamide was added, and the mixture was reacted for 3 h. The mixture was then washed with 10 mL of DMF and 30 mL of toluene in sequence. After filtration, the mixture was vacuum-dried at 100° C. overnight to obtain amino carbon nanotubes.

[0029] The preparation method of the high-refractive material is as follows: under a nitrogen atmosphere, 7.3 g of dithiothiadiazole is uniformly dissolved in 40 mL of anhydrous dichloromethane, 22 mL of triethylamine and 2.6 g of phthalic anhydride are added, and the mixture is stirred at -5°C for 0.75 h. 20 mL of a mixed solution of acryloyl chloride and dichloromethane in a volume ratio of 1:1 is slowly added dropwise using a dropping funnel. The mixture is reacted at room temperature for 24 h, and the solution is extracted 3 times with a 10% HCl aqueous solution to neutralize excess triethylamine, and then extracted 3 times with a saturated sodium chloride aqueous solution to obtain a high-refractive material.

[0030] Preparation method of chitosan / gelatin composite microspheres: (1) Dissolve 5.5 g of chitosan in 50 mL of 4% acetic acid aqueous solution, then dissolve 3.5 g of gelatin in 40 mL of deionized water at 55°C, and then mix the chitosan aqueous solution and the gelatin aqueous solution to form a chitosan / gelatin mixed solution; (2) Add 30 mL of paraffin and 5 g of span80 into a three-necked flask, heat to 55°C, stir for 30 min, and use a separatory funnel to drop the chitosan / gelatin mixed solution in step (1) into the three-necked flask. The dropping time is 15 min. Emulsify at 65°C for 35 min. After the emulsification is completed, quickly cool to 20°C, add 1 mL of 50% by mass glutaraldehyde, and cure for 0.75 h. After the curing is completed, centrifuge and collect the composite microspheres using a high-speed centrifuge, wash with acetone and isopropanol, and then dry to obtain chitosan / gelatin composite microspheres.

[0031] The prepared acrylic resin coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and a droplet test, cone calorimeter and other tests were performed.

[0032] Droplet test (1) Sample preparation: Place the prepared acrylic resin film in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h, then take it out and cut it into samples of 110 cm × 10 cm × 3 mm. Prepare 2 sets of samples, with 5 samples in each set.

[0033] (2) Parameters: Clamp about 5mm from the top so that the sample is vertically downward. Place a rosin board at the bottom of the sample, and pad about 0.3g of absorbent cotton on the board, evenly placed on the board. Adjust the gas flow rate to 105±5 mL / min so that the flame height reaches 20±1mm. Set the combustion time to 10s.

[0034] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button and enter the afterburning time. When the flame is completely extinguished, press the afterburning time end button and record the burning afterflame time and afterburning time.

[0035] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the cotton wool below will cause secondary combustion. Record the observation results.

[0036] The ASTM E1354-1990 (2004 standard) was used, and the cone calorimeter 2000 of the British FTT company was used for analysis and determination. The sample was 10cm×10cm, the thickness was 3mm, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 ,THR total heat release MJ / m², pSPR smoke generation rate reaches peak value m 2 / s and maximum total smoke release (TSR) m 2 / m 2 .

[0037] The yellowing resistance is determined by measuring the color change under ultraviolet light under simulated sunlight for 48 hours, using a HZ-3017 bulb-type yellowing resistance instrument.

[0038] The transmittance of the polymer film was tested using a UV-7504 ultraviolet-visible spectrophotometer to observe the transmittance at 450nm.

[0039] The refractive index of the film was tested using an Abbe refractometer.

[0040] The shrinkage rate of the film is the area of ​​the polyurethane emulsion formed into a film at 80°C and the area cooled to room temperature. The percentage of the difference between the area at room temperature and the area formed into a film at 80°C to the area formed into a film at 80°C is the shrinkage rate.

[0041] Table 1 Properties of the films formed by flame retardant, high refractive and drip resistant water-based acrylic resin coatings index Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example HkDJ 198.2 196.4 190.5 241.6 THR 26.4 28.9 31.5 36.8 Droplet situation No dripping No dripping No dripping No dripping pSPR smoke generation rate 0.08 0.09 0.10 0.12 TSR 112 108 114 120 Yellowing resistance (grade) 4.0 4.0 4.0 4.0 Oxygen index (%) 29.8 29.2 30.2 26.5 Refractive Index 1.69 1.71 1.72 1.51 Light transmittance (%) 95.2 95.8 96.1 94.1 Film shrinkage (%) 3.2 3.8 2.9 4.6 The comparative example is Example 1 of invention patent CN118813107B. It can be found from Table 1 that the flame retardant indicators such as pkHHR, THR, droplet condition, pSPR smoke generation rate and TSR generated by the combustion of the acrylic resin film obtained in Examples 1 to 3 of the present invention are better than those of the comparative example, and the refractive index indicators such as refractive index and transmittance are better, and the shrinkage rate of the film decreases less.

[0042] The third embodiment of the present invention is used for comparison.

[0043] Table 2 Film properties of flame retardant, high refractive, and drip-resistant acrylic resin coatings Embodiment 3 Element Burning droplet phenomenon Large amount of molten droplets Carbon nanotubes without amino group HkDJ 268.3 Carbon nanotubes without amino group THR 48.6 Carbon nanotubes without amino group pSPR smoke generation rate 0.324 Carbon nanotubes without amino group TSR 165.3 Carbon nanotubes without amino group Oxygen index (%) 28.6 Carbon nanotubes without amino group Burning droplet phenomenon There are molten drops but no dripping Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum HkDJ 242.6 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum THR 37.6 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum pSPR smoke generation rate 0.262 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum TSR 138.6 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum Oxygen index (%) 29.2 Add amino carbon nanotubes, without bis(2-ethylhexanoate)hydroxyaluminum Burning droplet phenomenon Melt without dripping Add amino carbon nanotubes, no acrylamide HkDJ 230.5 Add amino carbon nanotubes, no acrylamide THR 38.6 Add amino carbon nanotubes, no acrylamide Oxygen index (%) 29.3 Add amino carbon nanotubes, no acrylamide HkDJ 213.5 Add amino carbon nanotubes, without phosphorus trichloride Oxygen index (%) 28.4 Add amino carbon nanotubes, without phosphorus trichloride Oxygen index (%) 26.2 Without DOPO Oxygen index (%) 26.0 No APP added Oxygen index (%) 28.8 No aluminum sulfate added Oxygen index (%) 28.4 Without N-vinyl carbazole As can be seen from Table 2, amino carbon nanotubes, bis(2-ethylhexanoic acid) hydroxyaluminum, acrylamide, DOPO, APP, aluminum sulfate and N-vinyl carbazole all have a significant effect on improving the flame retardant properties of acrylic resins.

[0044] Table 3 Film-forming properties of flame-retardant, high-refractive, and drip-resistant acrylic resin coatings Embodiment 3 Ingredients Yellowing resistance (grade) 3.0 No high refractive material added Refractive Index 1.42 No high refractive material added Light transmittance (%) 91.8 No high refractive material added Yellowing resistance (grade) 3.5 Add high refractive material, but not acryloyl chloride Refractive Index 1.62 Add high refractive material, but not acryloyl chloride Light transmittance (%) 92.3 Add high refractive material, but not acryloyl chloride Yellowing resistance (grade) 3.0 Add high refractive material, but not dithiothiadiazole Refractive Index 1.46 Add high refractive material, but not dithiothiadiazole Light transmittance (%) 90.3 Add high refractive material, but not dithiothiadiazole Refractive Index 1.57 Add high refractive material, but not phthalic anhydride Yellowing resistance (grade) 3.5 Add high refractive material, but not phthalic anhydride It can be found from Table 3 that high-refractive materials, acryloyl chloride, phthalic anhydride and dithiothiadiazole have a great influence on the refractive resistance of acrylic resins. High-refractive materials increase the refractive index of acrylic resin segments and make the distribution of refractive monomer units more uniform.

[0045] Table 4 Film-forming properties of flame-retardant, high-refractive, and drip-resistant acrylic resin coatings Embodiment 3 Ingredients Film shrinkage (%) 4.6 Without N-vinyl carbazole Film shrinkage (%) 5.2 Without chitosan / gelatin composite microspheres As can be seen from Table 4, N-vinyl carbazole and chitosan / gelatin composite microspheres have a great influence on the shrinkage rate of acrylic resin films. The nitrogen-fused ring structure of N-vinyl carbazole makes it shrink less after curing and has good heat resistance. Chitosan / gelatin composite microspheres have the advantage of a small decrease in shrinkage under dry conditions, which reduces the decrease in the shrinkage rate of acrylic resin films at room temperature. In addition, the addition of ammonium molybdate increases the 96h precipitation of the acrylic resin emulsion, while the acrylic resin emulsion without ammonium molybdate has a small amount of precipitation after 96h.

Claims

1. A method for preparing a flame retardant, high refractive, and drip resistant aqueous acrylic resin coating, characterized in that: Prepare according to the following steps: (1) Preparation of core layer emulsion: Add 500-700 g of water, 13-19 g of emulsifier A, and 25-45 g of methacrylic acid into a reaction container, mix and stir evenly, heat to 50-55°C, stir and react for 30-60 min, then add monomer A, 13.4-14.5 g of DOPO, and 0.4-0.6 g of N-vinyl carbazole, and emulsify for 30-40 min; heat to 65°C, pass reflux water, heat to 75-85°C, dropwise add 12-14 g of initiator, dropwise add for 0.5-1.5 h, react for 1-2 h, and obtain core layer emulsion; (2) To the core layer emulsion obtained in step (1), 10-14 g of monomer B and initiator are added dropwise at the same time for 1-1.5 h, and the mixture is stirred at 70-85 °C for 1-2 h. Then 6.9-12.2 g of DOPO is added, and the mixture is reacted at 70-80 °C for 1-2 h. The mixture is cooled to 50 °C, and 14-21 g of emulsifier B is added for 30-60 min. Then 0.5-0.6 g of N-vinyl carbazole is added, and the mixture is reacted at 70-80 °C for 0.25-0.5 h. Then 14.2 g of ammonium polyphosphate solution dissolved in 10 g of water, 0.5-1.3 g of aluminum sulfate, 0.1-0.2 g of ammonium molybdate, and 0.5-0.8 g of chitosan / gelatin composite microspheres are added at 40-50 °C. 1000-2000 At a speed of r / min, high-speed shear emulsification is performed for 0.5-1h, and when the foam disappears, ammonia water is added to adjust the pH value to 7-8 to obtain a flame-retardant, high-refractive, and drip-resistant water-based acrylic resin coating; The monomer A is prepared by mixing 20-35g of ethyl acrylate, 22-38g of methyl methacrylate, 18-32g of hydroxyethyl acrylate, 6-12g of amino carbon nanotubes, and 3.4-6.2g of high refractive material; The monomer B is prepared by mixing 8-14g of amino carbon nanotubes, 12-54g of methyl methacrylate, 55-92g of hydroxyethyl acrylate and 3.2-5.8g of high refractive material.

2. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2.5:

1.

3. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: The method for preparing the amino carbon nanotubes is as follows: 0.7 g of carbon nanotubes were subjected to ultrasonic dispersion treatment for 2 to 3 h in concentrated sulfuric acid and 100 mL of concentrated nitric acid in a volume ratio of 3: 1 to 4:

1. After ultrasonication, the carbon nanotube solution was diluted with 100 mL of water, vacuum-filtered, washed with deionized water until neutral, and dried at 100 to 105° C. overnight to obtain carboxylated carbon nanotubes. 3.6 g of phosphorus trichloride was dissolved in 10 mL of DMF solution, 0.2 to 0.4 g of carboxylated carbon nanotubes and 4.5 to 4.7 g of bis(2-ethylhexanoic acid) hydroxyaluminum were added, reacted at 50 to 60° C. for 30 to 60 min, then placed in a constant temperature oil bath at 70 to 80° C., 7.7 to 9.4 g of acrylamide were added and reacted for 2 to 4 h, washed with 10 mL of DMF and 30 mL of toluene in turn, filtered, and vacuum-dried at 100 to 105° C. overnight to obtain amino carbon nanotubes.

4. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: The initiator is any one of ammonium persulfate and potassium persulfate.

5. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: The preparation method of the high-refractive material is as follows: under a nitrogen atmosphere, 7.3 g of dithiothiadiazole is uniformly dissolved in 40 mL of anhydrous dichloromethane, 22 mL of triethylamine and 2.2-2.9 g of phthalic anhydride are added, and the mixture is stirred at -5°C for 0.5-1 h. A dropping funnel is used to slowly dropwise add 20 mL of a 1:1 volume ratio of acryloyl chloride to dichloromethane solution, and the mixture is reacted at room temperature for 24 h. The reaction solution is then extracted 2-3 times with a 10% HCl aqueous solution to neutralize excess triethylamine, and then extracted 2-3 times with a saturated sodium chloride aqueous solution to obtain a high-refractive material.

6. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: The emulsifier B is AEO-9.

7. The method for preparing the flame-retardant, high-refractive, and drip-resistant aqueous acrylic resin coating according to claim 1, characterized in that: Preparation method of chitosan / gelatin composite microspheres: (1) Dissolve 5-6 g of chitosan in 50 mL of 4% by mass acetic acid aqueous solution, and dissolve 3-4 g of gelatin in 40 mL of deionized water at 55°C, then mix the chitosan aqueous solution and the gelatin aqueous solution to form a chitosan / gelatin mixed solution; (2) Add 30 mL of paraffin wax and 5 g of span80 into a three-necked flask, heat to 50-60°C, stir for 15-30 min, and slowly drip the chitosan / gelatin mixed solution in step (1) into the three-necked flask using a separatory funnel for 15 min. Emulsify at 60-70°C for 30-40 min. After emulsification, quickly cool to 20°C, add 1 mL of 50% glutaraldehyde, and solidify for 0.5-1 h. After solidification, centrifuge and collect the composite microspheres using a high-speed centrifuge, wash with acetone and isopropanol, and dry to obtain chitosan / gelatin composite microspheres.

Citation Information

Patent Citations

  • Naked-eye 3D display screen material and preparation method thereof

    CN111303478A

  • Preparation method of flame-retardant and light-resistant core-shell water-based acrylic resin coating

    CN118813107B

  • Magnetic water-soluble carbon nano tube as well as preparation method and application thereof

    CN103213967A

  • Carbon nano tube modified inflaming retarding optical cable material and preparation method thereof

    CN106084547A

  • Process for preparation of phosphorus-containing flame retardants and their use in polymer compositions

    CN114555613A

Cited By

  • Preparation method of heat-resistant, high-adhesion and high-conductivity acrylate resin adhesive

    CN121975463A